2021
DOI: 10.3390/molecules26185616
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Mucopolysaccharidoses: Pharmacological Implications

Abstract: Although mucopolysaccharidoses (MPS) are caused by mutations in genes coding for enzymes responsible for degradation of glycosaminoglycans, storage of these compounds is crucial but is not the only pathomechanism of these severe, inherited metabolic diseases. Among various factors and processes influencing the course of MPS, oxidative stress appears to be a major one. Oxidative imbalance, occurring in MPS and resulting in increased levels of reactive oxidative species, causes damage of various biomolecules, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Adenosine monophosphate (AMP) -activated protein kinase (AMPK) is an important regulator of cellular energy; AMPK activation helps to correct energy metabolism disorders. In response to cellular stress, AMPK can inhibit the expression of ROS by inducing endogenous antioxidant substances (11)(12)(13). Considering that ROS can directly participate in inflammation, autophagy, apoptosis, and other pathophysiological processes, AMPK activation may help to alleviate the above pathological processes.…”
Section: Original Articlementioning
confidence: 99%
“…Adenosine monophosphate (AMP) -activated protein kinase (AMPK) is an important regulator of cellular energy; AMPK activation helps to correct energy metabolism disorders. In response to cellular stress, AMPK can inhibit the expression of ROS by inducing endogenous antioxidant substances (11)(12)(13). Considering that ROS can directly participate in inflammation, autophagy, apoptosis, and other pathophysiological processes, AMPK activation may help to alleviate the above pathological processes.…”
Section: Original Articlementioning
confidence: 99%
“…Increased astrogliosis was observed in autopsies of patients and in a murine model, while microglia and T-cells have never been thoroughly investigated [ 261 , 262 , 263 ]. Studies have shown abnormalities in immune organs (e.g., spleen) and T-cell alterations in SMA mouse models, resulting in an abnormal neuroinflammatory response and exacerbation of the disease [ 264 ]. Importantly, functional studies investigating the status of T-cells and their protective or cytotoxic function in SMA may provide us insight on neuroinflammation in the pathogenesis of SMA.…”
Section: Pediatric Neurological Disordersmentioning
confidence: 99%
“…Unfolded protein response (UPR) and consecutive endoplasmatic reticulum (ER) stress may further contribute to cell disruption (Filippon et al, 2011;Pierzynowska et al, 2021).…”
Section: Inflammatory Immune Responsesmentioning
confidence: 99%